Exploring the Startup Costs and Profit of Bitcoin Mining in Urban Philippines - Taleon, Enrico Fernando C. (Animo Repository, 2021)
Bitcoin and other cryptocurrencies, with their promised easy income scheme, caught the attention of many nations along with the Philippines. The starting price of bitcoin and its profitability differed from nation to nation because of varied electricity costs, internet service providers, and currency value. The study aimed to explore the initial investment and the theoretical expected profit within one year of Bitcoin mining. The researchers used an exploratory research design and data mining techniques to gather quantitative data regarding the specifications of four different ASIC models, Meralco rates from September 2020, and monthly fees from the top three (3) internet service providers in the Philippines. The study did not cover industrial-sized cryptocurrency mining but instead, focused on an independent miner. The study found that theoretically, in one year, none of the ASIC’s yielded enough profit to have returned the initial investment. The Philippines’ higher than average internet service prices, electrical rates and market competition have jeopardized the profit in bitcoin mining. Hence, individual miners who do not join a mining pool put their investment at risk. A profit may have been established with other cryptocurrencies such as Etherium or cloud mining. A more sustainable and energy efficient Philippines could be the best answer to the dilemmas one could face with Bitcoin. If one could have easy access to sustainable power sources, a profit could be made stable and predictable.